1999
DOI: 10.1046/j.1432-1327.1999.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of cDNA clones encoding hydroxycinnamoyl‐CoA:tyramine N‐hydroxycinnamoyltransferase from tobacco

Abstract: The sequences of three cDNA clones that include the complete coding region of hydroxycinnamoylCoA:tyramine N-hydroxycinnamoyltransferase (THT) from tobacco are reported. The three cDNAs were isolated by antibody screening of a cDNA expression library produced from poly(A) + RNA purified from tobacco leaves (Nicotiana tabacum cv. Bottom Special), previously infiltrated with an incompatible strain of Ralstonia solanacearum. The identity of these clones was confirmed by the detection of THT activity in extracts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 44 publications
1
25
0
2
Order By: Relevance
“…Tyramine is sometimes listed as an aromatic component of suberin, being found as amide with phenylpropanoid acids (Kolattukudy, 2001;Bernards, 2002). However, genes for hydroxycinnamoyl-CoA:tyramine N-hydroxycinnamoyl transferases have been cloned and the proteins are members of the diamine acetyltransferase family (Farmer et al, 1999;Schmidt et al, 1999), so there is no need to postulate ASFT as an N-acyltransferase. Our Arabidopsis seed polyester monomer analyses were set up to recover tyramine, but none was observed (Molina et al, 2006).…”
Section: Asft Is a Feruloyl Transferase Involved In Suberin Biosynthesismentioning
confidence: 99%
“…Tyramine is sometimes listed as an aromatic component of suberin, being found as amide with phenylpropanoid acids (Kolattukudy, 2001;Bernards, 2002). However, genes for hydroxycinnamoyl-CoA:tyramine N-hydroxycinnamoyl transferases have been cloned and the proteins are members of the diamine acetyltransferase family (Farmer et al, 1999;Schmidt et al, 1999), so there is no need to postulate ASFT as an N-acyltransferase. Our Arabidopsis seed polyester monomer analyses were set up to recover tyramine, but none was observed (Molina et al, 2006).…”
Section: Asft Is a Feruloyl Transferase Involved In Suberin Biosynthesismentioning
confidence: 99%
“…One of the first genes encoding this type of enzyme to be characterized was the gene encoding tyramine:N-hydroxycinnamoyl transferase (THT; Hohlfeld et al, 1995;Schmidt et al, 1999;Yu and Facchini, 1999;Back et al, 2001;Von Roepenack-Lahaye et al, 2003;Kang et al, 2006). Analysis of their amino acid sequences revealed that all these enzymes belong to the GCN5-related N-acetyltransferases (GNAT) protein family, which also includes mammalian spermidine/spermine acetyltransferase and several microbial antibiotic N-acetyltransferases (Lu et al, 1996;Farmer et al, 1999;Kang et al, 2006). In contrast to the situation where PAs of arylamine moieties are mainly biosynthesized by the GNAT family of enzymes, the biosynthesis of the aliphatic type of phenolamides is exclusively the domain of BAHD acyltransferases (D'Auria, 2006;Bassard et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that THT enzymes have a broad range of substrate specificities and are encoded by a small gene family (Farmer et al, 1999;Schmidt et al, 1999). Tobacco and potato contain at least three THT isogenes, as shown by genomic Southern analyses.…”
Section: Discussionmentioning
confidence: 99%
“…AF329463) revealed 78% identity between the proteins. The protein has a high level of homology with THTs from other plants, including 83%, 80%, and 71% amino acid identity with tomato, potato, and tobacco THT proteins, respectively (Farmer et al, 1999;Schmidt et al, 1999;Von Roepenack-Lahaye et al, 2003). In the phylogenetic tree based on amino acid sequence of N-hydroxycinnamoyltransferases from four plant species, pepper SHT showed a greater evolutionary distance from pepper THT than other THTs within species (Fig.…”
mentioning
confidence: 96%
See 1 more Smart Citation